Building a Strong and Sustainable Brand: Effective Communication Strategies on Social Media in Improving Business Performance - Alhidayatullah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Social media has fundamentally reshaped marketing communication by enabling direct and interactive engagement between brands and consumers. With more than 4.9 billion global users, these platforms present both opportunities and challenges for organizations seeking to build sustainable brand relationships. This study examines the impact of effective communication strategies via social media on brand strength and corporate performance, while also assessing the mediating role of brand power in the relationship between communication strategy and business performance. The study emphasizes the significance of sustainable, engaging, and value-driven digital communications in establishing a robust brand within a competitive digital landscape. A quantitative study was administered to 138 MSMEs in Sukabumi that actively utilize social media for marketing purposes. Data analysis was conducted via the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique via SmartPLS software. The findings indicated that communication techniques significantly influenced brand strength and company performance, while the effect magnitude was smaller. Brand strength significantly influences business success and mediates the connection between communication strategy and business performance. A Q² value means the model’s superior prediction ability. These findings corroborate the Integrated Marketing Communication Theory (IMC) and Stakeholder Theory, offering strategic insights for sustainable brand growth via digital communication